Stress and its association with sociodemographic characteristics, coping and internet use among late adolescent university students in East Malaysia - Cheah, Whye Lian; Lai, H. Y. (Indian Association for Child and Adolescent Mental Health (India), 2019)
Introduction: Adolescents pursuing higher education at the university experience stressful life events on top of academic demands, where failure in managing those stressors can lead to stress as well as other more severe physical and mental health problems. Limited research exists locally about the association between coping and internet use with the perceived stress. Methodology: A cross-sectional study was conducted among 527 university students between 18-19 years old in Kota Samarahan. A self-administered questionnaire containing background information, perceived stress, measures of coping, motives of utilizing the internet, and internet addiction test was used. IBM SPSS version 23 was used for the data analysis. Result: The results showed that being female or having avoidant-emotional coping strategy was positively associated with perceived stress, whereas a problem-focused coping strategy was negatively associated with perceived stress. Internet addiction and underlying internet motives were not associated with perceived stress. Conclusion: The need to understand the association between coping and perceived stress is essential for professionals to assist adolescents in managing their mental health.